2014
DOI: 10.1167/iovs.13-13842
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Rho Kinase (ROCK) Inhibitor K-115: A New Candidate Drug for Neuroprotective Treatment in Glaucoma

Abstract: The results indicated that oral K-115 administration delayed RGC death. Although K-115 may be mediated through Nox1 downregulation, we found that it did not suppress ROS production directly. Our findings show that K-115 has a potential use in neuroprotective treatment for glaucoma and other neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 100 publications
2
85
1
1
Order By: Relevance
“…28 Mice were killed by cervical dislocation at 6 hours after ONI and eyes were enucleated. Retinas were isolated for a whole-mount preparation in cold PBS.…”
Section: Detection Of Oxidative Stress Using Cellrox Green Reagentmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Mice were killed by cervical dislocation at 6 hours after ONI and eyes were enucleated. Retinas were isolated for a whole-mount preparation in cold PBS.…”
Section: Detection Of Oxidative Stress Using Cellrox Green Reagentmentioning
confidence: 99%
“…28,31 To examine the effect of edaravone on ONI-induced ROS production, we performed staining of ROS using CellROX green reagent 31 in the wholemount retina. Because ROS is a powerful activator of ASK1-p38 MAPK signaling, we also performed CellROX green reagent analyses at 6 hours after ONI.…”
Section: Edaravone Suppresses Ros Production Following Onimentioning
confidence: 99%
“…[19][20][21][22] In addition, it has been reported that ripasudil exhibits neuroprotective effects for retinal ganglion cells following systemic administration in the rat optic nerve crush model. 23 A previous study with the radiolabeled drug showed that ripasudil reached the retina and choroid after eye drop administration in rabbits. 15,24 However, it is not known if ripasudil treatment inhibits ocular inflammation in the anterior chamber or retina, and the role of the Rho/ROCK pathway in ocular inflammation and leukocyte adhesion in EIU has not yet been clarified.…”
mentioning
confidence: 99%
“…33 Ripasudil is the first ophthalmic solution approved for the treatment of glaucoma and ocular hypertension in Japan; in 2014, it became available in an eye drop form to increase the outflow of the aqueous humor. [34][35][36] In addition, oral ripasudil protects RGCs after optic nerve injury by suppressing oxidative stress via Nox1 downregulation, 37 but there are few reports about its neuroprotective effects. In the present study, we found that topical ripasudil prevents glaucomatous retinal degeneration in EAAC1 KO mice by stimulating an IOP-independent pathway, in addition to IOPdependent pathways.…”
mentioning
confidence: 99%